Mechanisms of oxygen-dependent microbicidal system of neutrophils in the prognosis of acute pancreatitis - M. A. Shevlyaeva; G. K. Karipidi; S. V. Avakimyan; V. A. Zarubin; E. G. Ermolenko (Acta Biomedica Scientifica, 2012)
We observed 42 patients with, confirmed diagnosis of acute pancreatitis. We studied, the dynamics of spontaneous and stimulated. NBT-test and. the myeloperoxidase activity in conjunction, with, traditional clinical and. hardware methods of examination. The benchmarks of oxygen-enzyme systems of neutmphils and their conelation are important. Analysis of these indices makes it possible to predict the seventy of the disease, to determine the optimal timing opemtion and possible complications in the postoperative period.